Low caloric and protein intake is associated with mortality in patients with acute kidney injury - Bufarah, M. N.B. [UNESP]; Costa, N. A. [UNESP]; Losilla, M. P.R.P.; Reis, N. S.C. [UNESP]; Silva, M. Z.C. [UNESP]; Balbi, A. L. [UNESP]; Ponce, D. [UNESP] (Elsevier, 2018)
Background: Acute renal injury (AKI) interferes greatly with nutritional status, affecting the metabolism of all macronutrients and increased mortality rates in hospitalized patients. Our objective was to evaluate the association of nutritional parameters (albumin, cholesterol, caloric and protein intake and nitrogen balance (NB)) with mortality in patients with AKI. Methods: This is a prospective observational study that evaluated 595 consecutive patients over the age of 18 years with AKI, requiring enteral or parenteral feeding. At the time of the patient's enrollment, demographic and laboratorial data, caloric and protein supply and NB were recorded on the first day of referral to the nephrologist. All patients were followed throughout the hospital stay and mortality rate was also recorded. Results: The medium age of patients with AKI was 64 (54–75) years, 64.5% male, 62% admitted to intensive care unit (ICU), 52% on dialysis and the majority (48%) were at stage 3 by AKIN. Length of stay and hospital mortality were 18 (10–31) days and 46%, respectively. Superior age, AKI severity, lower body weight and body mass index (BMI), higher need for dialysis, ICU admission and shorter hospital stay were associated with higher mortality. At logistic regression, caloric (OR: 0.946; CI:95%: 0.901–0.994; p:0.029) and protein intake (OR: 0.947; CI:95%: 0.988–0.992; p = 0.028) and serum albumin (OR: 0.545; CI:95%: 0.401–0741; p < 0.001) were associated with hospital mortality. Cholesterol (OR: 0.995; CI:95%: 0.991–1.000; p = 0.052) was not associated with increased mortality in the adjusted analysis. Analysis of the receiver operating characteristic (ROC) curve showed that calorie intake < 12 kcal/kg (AUC: 0.745; CI:95%: 0.684–0.765; p < 0.001) and protein intake < 0.5 g/kg (AUC: 0.726; CI:95%: 0.686–0.767; p < 0.001) were predictors of hospital mortality, as well as a negative NB < −6.47 g N/day (AUC: 0.745; CI:95%: 0.704–0.786; p < 0.001). Conclusions: In conclusion, low caloric and protein intake, negative NB and low albumin value are conditions associated with higher hospital mortality in patients with AKI.
Keywords: Acute renal injury; Caloric intake; Mortality; Nitrogen balance; Protein intake